Structural and dielectric properties of PLD grown BST thin films. (January 2019) - Gupta, Reema; Gupta, Vinay; Tomar, Monika
Abstract: Thin films of Barium Strontium Titanate (BaSrTiO3, BST) have been deposited on platinised silicon substrate using pulsed laser deposition (PLD) technique. The effect of growth pressure and temperature during the film deposition on the crystallization and dielectric behaviour of the BST films has been studied. The effect of plume dynamics due to variation in deposition parameters present inside the deposition chamber has also been investigated. The dielectric constant of the BST thin film deposited under variable deposition pressures increases with increase in deposition temperature at a frequency of 1 MHz. The BST thin film deposited at 1.33 × 10 −4 bar and 800 °C substrate temperature exhibits high dielectric constant (≈475) with 65% tunability which can be efficiently exploited for the realization of tunable resonators and filters. Highlights: Barium strontium titanate (BST) thin films have been grown using Pulsed laser deposition technique. The dielectric properties of the BST thin films have been tuned by varying the growth conditions. The dynamics of the plasma plume are of significant interest for the growth of high quality thin films. The BST thin film deposited under optimized conditions exhibits high dielectric constant (≈ 475) with 65% tunability.